New ways of inhabiting the city as a result of continuous intra-urban migration and the social and cultural transformations (2019)
The main goal of this work is to study the continuous internal migrations that occur in the city as a result of the difficult life conditions in some communes and the social, cultural and urban transformations that have been developed under the concept of social innovation by different groups of designers, architects and by the municipal government. Also, to comprehend the new ways of inhabiting the city and the new appropriations of the territory, which generates new tensions and transgressions? The work allows us to understand the relation between the migrations, the social transformations and the new ways of inhabiting the territory in Medellin, defining it as a territory as a common space, delimited and defined throughout the relationships that exist between the individuals that inhabit it.